Differential contributions of the inferior parietal and inferior frontal regions to the processing of grammatical and semantic relationships in wh-questions - Kambara, Toshimune; Tsukiura, Takashi; Yokoyama, Satoru; Takahashi, Kei; Shigemune, Yayoi; Miyamoto, Tadao; Takahashi, Daiko; Sato, Shigeru; Kawashima, Ryuta (Language sciences (Oxford), 2013)
► Grammatical processing of wh-questions associated with left inferior parietal activity. ► Semantic processing of wh-questions associated with left inferior frontal activity. ► Interactions between these activities are significant in the processing of wh-questions. The processing of grammatical and semantic relationships is important in sentence comprehension. Although previous studies have demonstrated brain activities during grammatical and semantic processing in declarative sentences, functional MRI (fMRI) evidence related to these processes in wh-questions is largely unavailable. In Japanese wh-questions, a wh-phrase is grammatically associated with the closest particle, and a sentential subject is semantically associated with the verb. These features in Japanese wh-questions enable us to make grammatical or semantic anomalies without adding other words or morphemes in the violation paradigm. According to this advantage of Japanese wh-questions, this fMRI study investigated the brain activities in Japanese native speakers during grammatical and semantic processing of wh-questions to judge whether or not presented sentences were natural Japanese sentences (naturalness decision task). Three types of wh-questions were presented: correct, grammatically anomalous, and semantically anomalous conditions. This study yielded three main findings. First, activity in the left inferior parietal lobule was greater during processing of grammatically anomalous than correct or semantically anomalous wh-questions. Second, activity in the left inferior frontal gyrus was greater during processing of semantically anomalous than correct or grammatically anomalous wh-questions. Finally, significant correlations were identified between activities in the left inferior parietal lobule and the left inferior frontal gyrus during grammatically anomalous and semantically anomalous wh-questions. These findings suggest that the left inferior parietal and inferior frontal regions have differential contributions to the processing of grammatical and semantic relationships in wh-question sentences, and that the interaction between these regions could be essential in the comprehension of wh-questions by combining the grammatical process with the semantic process.